2020
DOI: 10.3390/en13123106
|View full text |Cite
|
Sign up to set email alerts
|

Do Oil Price Shocks and Other Factors Create Bigger Impacts on Islamic Banks than Conventional Banks?

Abstract: The main aim of this study is to empirically examine and compares the impacts of oil price shocks, Arab revolutions, some macroeconomics, and bank-specific variables on bank profitability indicators between Conventional and Islamic banks in Gulf Cooperation Council (GCC) countries. The study employed panel Autoregressive-Distributed Lag (ARDL) techniques to examine the causal relationship both at the short and long-run. Our results reveal that most of the variables employed in our study significantly influence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(8 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…According to the case of banks operating in Gulf Cooperation Council countries, the oil price remains one of the significant factors influencing banks' profitability. Additionally, the influence of macroeconomic factors on banks' profitability is proven for Islamic Banks (Esmaeil et al 2020). The authors revealed the similarities in the influence of attitudinal factors on the profitability of conventional and Islamic banks.…”
Section: International Empirical Researchmentioning
confidence: 95%
“…According to the case of banks operating in Gulf Cooperation Council countries, the oil price remains one of the significant factors influencing banks' profitability. Additionally, the influence of macroeconomic factors on banks' profitability is proven for Islamic Banks (Esmaeil et al 2020). The authors revealed the similarities in the influence of attitudinal factors on the profitability of conventional and Islamic banks.…”
Section: International Empirical Researchmentioning
confidence: 95%
“…Further, Ref. [ 49 ] found that CBs were more adversely affected by oil price shock and Arab spring than IBs. This result indicates that IBs’ profitability is more resilient than CBs, due to their higher speed of adjustment to equilibrium in the event of any shock.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Though there is a considerably different influence of oil-exporting and importing economies on the exchange rate movement [ [42] , [43] , [44] ]. An increasing trend in oil prices caused an appreciation of domestic currency for the oil-exporting economy [ 45 ]. In contrast, an oil-importing economy will increase trade deficits that cause a debt burden and eventually depreciate the currency.…”
Section: Literature Reviewmentioning
confidence: 99%